Occupational risk factors for work disability following carpal tunnel syndrome: a pooled prospective study. Issue 7 (24th January 2022) - Harris-Adamson, Carisa; Eisen, Ellen A; Kapellusch, Jay; Hegmann, Kurt T; Thiese, Matthew S; Dale, Ann-Marie; Evanoff, Bradley; Meyers, Alysha Rose; Bao, Stephen; Gerr, Fred; Krause, Niklas; Rempel, David
Abstract : Background: Although recent studies have identified important risk factors associated with incident carpal tunnel syndrome (CTS), risk factors associated with its severity have not been well explored. Objective: To examine the associations between personal, workplace psychosocial and biomechanical factors and incident work disability among workers with CTS. Methods: Between 2001 and 2010 five research groups conducted coordinated prospective studies of CTS and related work disability among US workers from various industries. Workers with prevalent or incident CTS (N=372) were followed for up to 6.4 years. Incident work disability was measured as: (1) change in work pace or work quality, (2) lost time or (3) job change following the development of CTS. Psychosocial factors were assessed by questionnaire. Biomechanical exposures were assessed by observation and measurements and included force, repetition, duty cycle and posture. HRs were estimated using Cox models. Results: Disability incidence rates per 100 person-years were 33.2 for changes in work pace or quality, 16.3 for lost time and 20.0 for job change. There was a near doubling of risk for job change among those in the upper tertile of the Hand Activity Level Scale (HR 2.17; 95% CI 1.17 to 4.01), total repetition rate (HR 1.75; 95% CI 1.02 to 3.02), % time spent in all hand exertions (HR 2.20; 95% CI 1.21 to 4.01) and a sixfold increase for high job strain. Sensitivity analyses indicated attenuation due to inclusion of the prevalent CTS cases. Conclusion: Personal, biomechanical and psychosocial job factors predicted CTS-related disability. Results suggest that prevention of severe disability requires a reduction of both biomechanical and organisational work stressors.